Effectiveness of Using the Quizzz Application in Islamic Religious Education - Qurroti A'yun; Sulastri Sulastri; Diana Eka Wati; Dwi Ratna Sari; Hanif Ma'rufa; Faizah Nur Khafidhloh (Sultan Publisher, 2022)
Since the Covid-19 pandemic, in human life there have been many influences in the field of education—both in the form of systems and characters, as well as the learning media used. Every time there is a change, it is sure that there will be an innovation regarding learning media which is, of course, IT-based. This research was conducted to determine the effectiveness of the Quiziz application media in Islamic Religious Education subjects in improving student learning outcomes at SMA Negeri 7 Malang. This research uses descriptive quantitative methods, with data collected through observation, documentation and questionnaires. Data sourced from this study were taken from students and students of class X SMA Negeri 7 Malang. Based on the results of research conducted by researchers, it can be concluded that: (1) learning media using the Quizizz application can be applied in teaching and learning activities because the Quizizz application is an interactive and fun application in which there are various features such as quizzes, surveys, games and discussions. (2) in its application, learning media using the Quizizz application is quite liked by students. (3) from the results of this study, the researcher feels that learning media using the Quizizz application is very effective and can increase the motivation and desire of students to understand and explore the subject matter given by the teacher, especially Islamic Religious Education subjects.